Evaluating acute toxicity and hepatoprotective effect of Ich can thanh oral solution in a paracetamol-induced acute hepatitis mouse model - Tung, Tran Thanh; Loan, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2026)
This study investigated the acute toxicity and hepatoprotective effect of Ich can thanh oral solution in a mouse model of paracetamol-induced acute hepatitis. The acute toxicity was assessed through oral administration, and the median lethal dose (LD50) was estimated using the Litchfield-Wilcoxon method. In the paracetamol-induced acute hepatitis model, mice were randomly divided into experimental groups and pretreated orally with distilled water, silymarin (140 mg/kg), or Ich can thanh (4.8 or 9.6 mL/kg/day) for eight consecutive days. Acute liver injury was induced by oral administration of paracetamol (400 mg/kg). Forty-eight hours after induction, serum biochemical parameters, liver weight, hepatic malondialdehyde (MDA) and glutathione (GSH) levels and histopathological changes were assessed. No mortality or toxic signs at doses up to 120 mL/kg (approximately 25 times higher than the intended human dose), indicating that LD50 exceeds the highest tested dose. Additionally, Ich can thanh 4.8 mL/kg/day showed a trend towards hepatoprotection, whereas 9.6 mL/kg/day significantly reduced liver weight, decreased AST and ALT activities, increased serum albumin levels, attenuated lipid peroxidation, and improved liver histopathological compared with the model group. In conclusion, Ich can thanh, particularly at 9.6 mL/kg/day, exerts significant hepatoprotective effects in a mouse model of paracetamol-induced acute liver injury.